Three-Month Endothelial Human Endothelin-1 Overexpression Causes Blood Pressure Elevation and Vascular and Kidney Injury. Issue 1 (January 2018) - Coelho, Suellen C.; Berillo, Olga; Caillon, Antoine; Ouerd, Sofiane; Fraulob-Aquino, Júlio C.; Barhoumi, Tlili; Offermanns, Stefan; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Endothelium-derived endothelin (ET)-1 has been implicated in the development of hypertension and end-organ damage, but its exact role remains unclear. We have shown that tamoxifen-inducible endothelium-restricted human ET-1 overexpressing (ieET-1) mice exhibited blood pressure rise after a 3-week induction in an ET type A (ETA ) receptor-dependent manner, in absence of vascular and renal injury. It is unknown whether long-term ET-1 overexpression results in sustained blood pressure elevation and vascular and renal injury. Adult male ieET-1 and control tamoxifen-inducible endothelium-restricted Cre recombinase (ieCre) mice were induced with tamoxifen and 2.5 months later, were treated with or without the ETA receptor blocker atrasentan for 2 weeks. Three-month induction of endothelial human ET-1 overexpression increased blood pressure ( P <0.01), reduced renal artery flow ( P <0.001), and caused mesenteric small artery stiffening ( P <0.05) and endothelial dysfunction ( P <0.01). These changes were accompanied by enhanced mesenteric small artery Col1A1 and Col3A1 expression, and perivascular adipose tissue oxidative stress ( P <0.05) and monocyte/macrophage infiltration ( P <0.05). Early renal injury was demonstrated by increased kidney injury molecule-1 expression in renal cortex tubules ( P <0.05), with, however, undetectable lesions using histochemistry staining and unchanged urinary albumin. There was associated increased myeloid (CD11b + ) and myeloid-derived suppressive cell (CD11b + Gr-1 + ) renal infiltration ( P <0.01) and greater frequency of myeloid and renal cells expressing the proinflammatory marker CD36 ( P <0.05). Atrasentan reversed or reduced all of the above changes ( P <0.05) except the endothelial dysfunction and collagen expression and reduced renal artery flow. These results demonstrate that long-term exposure to endothelial human ET-1 overexpression causes sustained blood pressure elevation and vascular and renal injury via ETA receptors. Abstract : Supplemental Digital Content is available in the text.